The Effectiveness of The Experiential Learning and Cooperative learning Activities in Developing English Speaking Skills for Students SMA Parulian 2 Medan - Hulu, Imarson (Pascasarjana Universitas HKBP Nommensen, 2022)
In recent years, with the rapid development of the economy in Indonesia, English language is consideredas an effective tool to help students find a good job with high income. Many studies on how to improvelearners’ speaking skill shave been carried out among educational researchers in the world and VietNam. However, whether these innovative activities really improve students’ speaking skills at ThaiNguyen University has not been fully investigated. Therefore, this study paper introduces a study on theimproving students’ speaking skills through experiential learning activities of the academic year 2016-2017. The experimental learning, a method was used since it involved the gathering of information aboutthe present conditions. It described the nature of the situation as it existed at the time of the study. Itaimed to determine the effectiveness of using experiential learning activities in improving students’speaking skill at SMA Parulian 2 Medan. The main source of data was the questionnaire and observationto be developed by the writer.